Labeled oxytocin administered via the intranasal route reaches the brain in rhesus macaques - M. R. Lee (Nature Portfolio, 2020)
The location and extent of intranasal oxytocin brain penetrance has not been shown. Here the authors show that oxytocin, administered intranasally, enters brain regions along the trajectories of the olfactory and trigeminal nerves and there, reaches biologically relevant concentrations.